2014
DOI: 10.1093/cercor/bhu095
|View full text |Cite
|
Sign up to set email alerts
|

The Neonatal Connectome During Preterm Brain Development

Abstract: The human connectome is the result of an elaborate developmental trajectory. Acquiring diffusion-weighted imaging and resting-state fMRI, we studied connectome formation during the preterm phase of macroscopic connectome genesis. In total, 27 neonates were scanned at week 30 and/or week 40 gestational age (GA). Examining the architecture of the neonatal anatomical brain network revealed a clear presence of a small-world modular organization before term birth. Analysis of neonatal functional connectivity (FC) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
247
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 345 publications
(291 citation statements)
references
References 113 publications
(169 reference statements)
39
247
4
1
Order By: Relevance
“…Most infants are scanned during natural sleep or after administering mild sedation (25-60 mg/kg oral chloral hydrate) (Doria et al, 2010a;Toulmin et al, 2015;van den Heuvel et al, 2014) and although appropriate measures are generally taken to reduce motion artifacts including feeding and swaddling (where infants are scanned during natural sleep), wrapping the infant in a vacuum fixation pillow and applying hearing protection devices to reduce exposure to acoustic noise, even subtle head movement remains a significant problem. Furthermore, the use of sedative medication -if administered -is generally confined to infants scanned in a clinical setting and may thus introduce a bias in terms of the effect of motion, as well as differences in physiological parameters and sleep state/level of consciousness between health and disease states.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most infants are scanned during natural sleep or after administering mild sedation (25-60 mg/kg oral chloral hydrate) (Doria et al, 2010a;Toulmin et al, 2015;van den Heuvel et al, 2014) and although appropriate measures are generally taken to reduce motion artifacts including feeding and swaddling (where infants are scanned during natural sleep), wrapping the infant in a vacuum fixation pillow and applying hearing protection devices to reduce exposure to acoustic noise, even subtle head movement remains a significant problem. Furthermore, the use of sedative medication -if administered -is generally confined to infants scanned in a clinical setting and may thus introduce a bias in terms of the effect of motion, as well as differences in physiological parameters and sleep state/level of consciousness between health and disease states.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…With all major white matter tracts being in place by the end of normal gestation, it is not surprising that structural connectome studies -examining whole brain connectivity on a macroscopic level (Box 1) -have revealed structural network organization in the neonatal brain to show great similarity to the adult human brain Brown et al, 2014;Ratnarajah et al, 2013;Shi et al, 2012;Tymofiyeva et al, 2012;van den Heuvel et al, 2014;Yap et al, 2011). Key features of adult connectome architecture have been demonstrated in the neonatal brain, including a small world organization -combining local specialization with long-range efficiency -, a modular topology -meaning that the network constitutes smaller subnetworks for specialized information processing -, and a heavy tailed degree distribution with brain regions which show the highest number of connections forming a central core or 'rich club' (Box 1).…”
Section: Postnatal Brain Developmentmentioning
confidence: 99%
See 3 more Smart Citations